Simulation and Study of Natural Fire in a Wide-Framed Multipurpose Hall with Steel Roof Trusses - D. Pada (Acta Polytechnica, 2009)
In this case study, the structural fire safety of unprotected steel roof trusses in a wide-framed multipurpose hall was evaluated according to the natural fire safety concept. The design fires were simulated with FDS in order to determine the temperature development inside the hall. The temperature of the steel was calculated based on the results from the simulation and the structural analysis was carried out in Robot. It was established that the steel roof trusses could be left unprotected under certain conditions, however, a more violent design fire resulted in failure of the truss.